Contribution To The Study Of The Biodiversity Of Benthic Invertebrates And The Biological Quality Of Some Rivers In The Watershed Boumerzoug (east Of Algeria) - Bekhouche, N.; Marniche, F.; Ouldjaoui, A. (University of Eloued جامعة الوادي, 2017)
The composition of invertebrate communities colonizing the bottom of rivers, called for this reason benthic macro invertebrates, allows characterizing the biological quality of river water.This study focuses on benthic macrofauna of oued Boumerzoug and its two tributaries: Oued El Guareh and Oued Segus. Eleven (11) stations were prospecting object, between December 2014 and April 2015.The six sampling campaigns have identified a faunal population consisted of 7364 individuals, distributed in 106 taxa, with predominance of Diptera and the lack of sensitive polluo- elements (plécoptères). The results of analysis by method " IBGN " reveal poor hydro biological quality in the stations (G1, G2, G3, S1, S2, S3, S4, B1) and bad qualities for stations (B2, B3, B4).
Article in Journal of Fundamental and Applied Sciences Vol 09, N 01
Keywords: Benthic macro-invertebrates ; Bio- indicators ; Pollution ; IBGN ; Quality.